Paradigmas de la protección de datos personales en Ecuador. Análisis del proyecto de Ley Orgánica de Protección a los Derechos a la Intimidad y Privacidad sobre los Datos Personales (Tema Central) - Enríquez Álvarez, Luis Fernando (2017)
Ecuador urgently needs to create a data protection law to protect the rights of natural persons in relation to the processing, conservation, and explotation of their personal data by public and private institutions. Our country is required to comply with minimum standards in order to be considered as a trusted country for personal data transfers, allowing the emergence of transnational Ecuadorian enterprises treating personal data of foreign citizens from worldwide on Internet. This article aims to analyze some missconceptions of the project named Ley Orgánica de Protección de los Derechos a la Intimidad y Privacidad sobre los Datos Personales with the purpose of recommend some corrections. Furthermore, this article proposes the creation of a data protection act which is synchronized with other countries laws, and the technical reality of information technologies.